Improving the Students’ Speaking Skill by Implementing Snowball Throwing Technique - Fitriya, Fitriya; Hayuningtyas, Nina; Khodijah, Siti (Critical Review of English-Arabic World Journal, 2022)
The aim of this research was to find out whether the implementation of Snowball throwing technique can improve students’ speaking skill among the eight grade students of SMP Nurul Islam Jember. The focused on this research is speaking skill. This research was classified as Classroom Action Research (CAR) of Kemmish and Taggart which consisted of four procedures, namely planning the action, implementing the action, observing and reflecting. In this research, the researcher conducted two cycles. The cycle was applied on November 2020 which consisted of three meetings, two meetings for implementing the action and one meeting for students’ speaking test or post test. The result of this research showed that there was improvement of the students’ speaking skill. It could be seen from the result of the test which improved. The mean score of the pre-test was 55.46 the mean score of post-test 1 was 65.35. The mean score of post-test 2 was 79.46. The precentage of students who passed the minimum score in pre-test was 21%, in cyle 1 was 46%, and cycle 2 was 78%. It can be conclouded that there were improvement of students’ speaking skill by implementing snowball throwing technique.